Robbery and Bullying: Protection Through Pageu Gampong Customary Law, and Islamic Law - Abdullah, M Adli; Mansur, Teuku Muttaqin; Sulaiman, Sulaiman; Usman, Musliadi Bin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
The social resilience system of the Acehnese people is rooted in the pageu gampong tradition. The values of pageu gampong are defined as how the people of Aceh protect themselves from the flow of criminal behavior, robbery, bullying and community supervision based on customary law. This research aims to reveal the facts, situations and phenomena of robbery and bullying behavior in Acehnese society through the protection of the pageu gampong customary system. Data was collected through interviews and analyzed using a juridical-sociological and phenomenological approach. The results of the research show that the practice of robbery and bullying is influenced by lifestyle demands accompanied by economic limitations and weaknesses in socializing in society, due to neglect of the values contained in the pageu gampong tradition. Pageu gampong as a customary law system has values that are integrated with Islamic values and is able to protect the community from all forms of robbery and bullying behavior. However, the tendency of the legal system to be oriented towards positivism and the current pressure for social change also contributed to the fading of the values of pageu gampong as the strength of the social structure of Acehnese society. The values of pageu gampong still survive in Acehnese society which is under the legal system of the Acehnese government.